Design of high-performance electro-driven nanofiltration membrane via facile co-deposition of pyrogallol and polyethyleneimine for sustainable resource recovery from landfill leachate concentrate - Jiale Du; Zijian Yu; Jiangjing Li; Shuangling Xie; Lianxin Chen; Jiuyang Lin (Advanced Membranes)
Conventional treatment methods of landfill leachate concentrate mainly focus on the degradation or removal of humic substance, which are prone to secondary pollution and fail to meet the requirements of current sustainable development. The key to sustainable management of landfill leachate concentrate is to precisely fractionate the existing humic substance and inorganic salts as individual resources. Here, electro-driven nanofiltration membranes were fabricated by sodium periodate inducing co-deposition of pyrogallol and polyethyleneimine on the loose polyamide-based nanofiltration substrate membranes as high-performance anion conducting membrane. The pyrogallol/polyethyleneimine composite coating layer endowed the electro-driven nanofiltration membranes with reduced surface negative charge and specific areal electric resistance for enhanced anion transfer. During the electro-driven nanofiltration process, the fabricated membrane with a 30-min co-deposition exhibited an extremely fast anion transfer rate and outstanding fractionation performance with 99.08 ​% humic substance recovery of 99.08 ​%. Particularly, the fabricated membrane showed stable separation capacity over an 8-cycle electro-driven nanofiltration operation, demonstrating a low fouling propensity. Our study sheds light on the strategy to fabricate high-performance electro-driven nanofiltration membranes via co-deposition of pyrogallol and polyethyleneimine, paving the way to sustainable treatment of landfill leachate concentrate.